PENGARUH DAMPAK COVID-19 DARI SEGI EKONOMI DAN PENDIDIKAN TERHADAP KEMAUAN VAKSIN MASYARAKAT DI KELURAHAN DABO LAMA SINGKEP KABUPATEN LINGGA KEPULAUAN RIAU - Abdul Zaky; Angela Huljannah; Yuni Asnita Adetia Safitri; Sylvi Chairuniza Lubis (LPPM Universitas Awal Bros, 2021)
The first case of COVID-19 appeared in Wuhan, Hubei Province, China at the end of 2019. The disease is caused by a new corona virus (CoV) named Severe Acute Respiratory Syndrome Corona Virus 2 (SARSCOV-2) (Maugeri et al., 2020). It is transmitted between humans with an incubation period of 1-14 days and the symptoms are felt on the 3rd day to the 7th day. Transmission of this virus is through droplets of an infected person when talking, coughing, sneezing, and through contact and touch. Delays in vaccine distribution can result in considerable mortality and morbidity as illustrated by the 2013/2014 West African Ebola epidemic which killed more than 11,000. Therefore COVID-19 has a major impact on public health, which will also affect economic, educational and living conditions. Indonesian society. Currently, the world is experiencing extraordinary life-changing challenges due to the Covid-19 pandemic. This research uses quantitative research, because information or data is realized in the form of numbers and analyzed based on statistical analysis. Because the calculated chi square value is 40,096 > chi square table 21.0261, then as the basis for the decision above, it can be concluded that HO is rejected and Ha is accepted. Vaccination. Thus, it can be interpreted that there is a relationship between the impact of Covid-19 and the willingness of vaccines in the community area in the Dabo Lama Singkep Village, Lingga Regency, Riau Islands.